(x+23)+(x+61)=180

Simple and best practice solution for (x+23)+(x+61)=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+23)+(x+61)=180 equation:


Simplifying
(x + 23) + (x + 61) = 180

Reorder the terms:
(23 + x) + (x + 61) = 180

Remove parenthesis around (23 + x)
23 + x + (x + 61) = 180

Reorder the terms:
23 + x + (61 + x) = 180

Remove parenthesis around (61 + x)
23 + x + 61 + x = 180

Reorder the terms:
23 + 61 + x + x = 180

Combine like terms: 23 + 61 = 84
84 + x + x = 180

Combine like terms: x + x = 2x
84 + 2x = 180

Solving
84 + 2x = 180

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-84' to each side of the equation.
84 + -84 + 2x = 180 + -84

Combine like terms: 84 + -84 = 0
0 + 2x = 180 + -84
2x = 180 + -84

Combine like terms: 180 + -84 = 96
2x = 96

Divide each side by '2'.
x = 48

Simplifying
x = 48

See similar equations:

| .5y=8+6x | | 12x+2+43x+1=168 | | 0.33(6x+12)-2(x-7)=19 | | 7k+16-10k+5= | | 2A=(24)(7) | | 13(1.51+0.51z+z)=9 | | 2x-3=3x+2+x | | Z-5z=7z-9x-z | | 6(2c+4)=18 | | 1/2(x-3)=5/15+(2/3)(2x-5) | | 2x^2+15x+6.25=0 | | 18z+12z-9= | | 5(1-3r)=-85 | | x+20+23+x+21=x+32 | | 7u+6v-9(7u-5v+4w)= | | 49=4v+13 | | 3(3x+6)=6(5x+2) | | (x+24)+(x+61)=180 | | x+3+x+11+1=x+14 | | 9w-w= | | 6x-[3x+8]=16 | | C=2ur | | 14k+9=k+15 | | 4x-98=37+13x | | (6x^3+7)(8x)= | | 14+16z-13-10z= | | 14.2+25.2=3.8t+26.8 | | 4K-8=-8+4K-K | | w/5-17=5 | | 3x+6=4(x+2)+5x | | 8x+9=4(x+6)-3x | | 2x-10+2x-9+25=2x-16 |

Equations solver categories